2005
DOI: 10.1038/sj.hdy.6800733
|View full text |Cite
|
Sign up to set email alerts
|

No detectable genetic correlation between male and female mating frequency in the stalk-eyed fly Cyrtodiopsis dalmanni

Abstract: There is much interest in explaining why female insects mate multiply. Females of the stalk-eyed fly Cyrtodiopsis dalmanni can mate several times each day in a lifetime which may span several months. There are many adaptive explanations, but one hypothesis that has received little rigorous empirical attention is that female multiple mating has evolved for nonadaptive reasons as a correlated response to selection for high male mating frequency rather than because of direct or indirect benefits accruing to femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The original proposition that female promiscuity might evolve as a genetic corollary of selection on male promiscuity (8, 18) has been criticized for its assumption that the same physiological mechanisms would underlie mating behavior in each sex (19). In apparent support of this criticism, a range of studies have failed to find a positive genetic correlation between male and female mating speed or mating frequency in chicken (20), Drosophila (21), stalk-eyed flies (22), and bean beetles (23). Only one study on mating frequency in burying beetles (24) has found a strong between-sex genetic correlation, although mating frequency was measured here with the same partner rather than with different partners.…”
Section: Discussionmentioning
confidence: 99%
“…The original proposition that female promiscuity might evolve as a genetic corollary of selection on male promiscuity (8, 18) has been criticized for its assumption that the same physiological mechanisms would underlie mating behavior in each sex (19). In apparent support of this criticism, a range of studies have failed to find a positive genetic correlation between male and female mating speed or mating frequency in chicken (20), Drosophila (21), stalk-eyed flies (22), and bean beetles (23). Only one study on mating frequency in burying beetles (24) has found a strong between-sex genetic correlation, although mating frequency was measured here with the same partner rather than with different partners.…”
Section: Discussionmentioning
confidence: 99%
“…Second, given the high levels of male harassment under laboratory conditions, multiple mating may have evolved as a way of limiting costly harassment, as envisaged by the convenience polyandry hypothesis (Thornhill & Alcock 1983). Third, the evolution of polyandry may be a pleiotropic effect of some other laboratory-induced change, and so not under direct selection at all (Halliday & Arnold 1987;Grant et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the results of artificial selection experiments are mixed and provide no clear evidence for a genetic correlation between the sexes in mating frequency in D. melanogaster. In the stalk-eyed fly, Cyrtodiopsis dalmanni, artificial selection for male mating frequency produced no correlated response in female mating frequency (Grant et al, 2005). So far, only these data are available to determine a genetic correlation between the sexes in mating frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, females may evolve to mate more frequently than their optima under stronger selection for mating frequency in males than in females (Halliday and Arnold, 1987;Halliday, 1988, 1992). This nonadaptive hypothesis is controversial (Sherman and Westneat, 1988;Cheng and Siegel, 1990;Gromko, 1992;Schwartz and Boake, 1992) and has received only a little empirical attention (Grant et al, 2005), in contrast to the adaptive hypotheses that have been investigated extensively (see, for example, Arnqvist and Nilsson, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation